Multi-scale approach from mechatronic to Cyber-Physical Systems for the design of manufacturing systems - Penas, Olivia; Plateaux, Régis; Patalano, Stanislao; Hammadi, Moncef (Computers in industry, 2017)
Recent advances in manufacturing industry, and notably in the Industry 4.0 context, promote the development of CPSs and consequently give rise to a number of issues to be solved. The present paper describes the context of the extension of mechatronic systems to cyber-physical ones, firstly by highlighting their similarities and differences, and then by underlining the current needs for CPSs in the manufacturing sector. Then, the paper presents the main research issues related to CPS design and, in particular, the needs for an integrated and multi-scale designing approach to prevent conflicts across different design domains early enough within the CPS development process. To this aim, the impact of the extension from mechatronic to Cyber-Physical Systems on their design is examined through a set of existing related modelling techniques. The multi-scalability requirement of these techniques is firstly described, concerning external/internal interactions, process control, behaviour simulation, representation of topological relationships and interoperability through a multi-agent platform, and then applied to the case study of a tablets manufacturing process. Finally, the proposed holistic description of such a multi-scale manufacturing CPS allows to outline the main characteristics of a modelling-simulation platform, able notably to bridge the semantic gaps existing between the different designing disciplines and specialised domains.